Comparative study between combination of famciclovir and prednisolone with prednisolone alone in acute Bell's palsy. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):605-13 The abstract of this article is available on the PubMed website